(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The long history of Chinese immigrants in Mexico has been observed, from historiography, linked to the national state building in the postrevolution period. The campaigns against their presence on Mexican soil, and their xenophobic character contrast with other processes in some parts of the Republic as in the case of Chiapas, where the Chinese were gradually incorporated to the host society. Some organizations helped in this integration. However, the current debates on the nature of the Chinese ethnic group in Mexico distort, rather than help, to understand what happened. For this reason, the article seeks to present evidence about that historical process. At the same time it discusses the ethnic definitions people apply in the present.